THE EFFECT OF FAMILY HARMONY AND SCHOOL ENVIRONMENT ON STUDENTS’ LEARNING OUTCOMES IN MATHEMATICS SUBJECT - Mukmina Mukmina; Sitti Inaya Masrura; Nurfadilah Mahmud (MaPan : Jurnal Matematika dan Pembelajaran, 2021)
This study aimed to determine the effect of family harmony and school environment on students learning outcomes in mathematics for grade VII SMP Negeri 2 Tinambung. This research is an ex post facto research, causal-comparative research with a research sample of 70 students selected using probability sampling (proportionate stratified random sampling). The data collection techniques used the family harmony questionnaire, school environment questionnaire, and mathematics learning outcomes test. The data analysis techniques use descriptive and inferential statistical analysis. The results of this study are (1) family harmony has a positive and significant effect on student learning outcomes in mathematics, (2) the school environment has a positive and significant effect on student learning outcomes in mathematics, and (3) family harmony and school environment together have a positive and significant effect on students learning outcomes in mathematics. The recommendation is to create a good school environment to support the learning process. Also, efforts should be made to harmonize families by conducting joint activities with all family members, love each other, create a peaceful home atmosphere, build good and open interaction and communication between family members so that it is possible for children to get a good atmosphere in learning in order to achieve better learning outcomes.